The Impact of Use of Chatgpt on Changes in Students' Learning Behavior - Assegaf, Syaipul; Mara Qonitatillah; Nurlita Nazma Prameswari; Bayu Kurniawan; Nurul Ratnawati (International Journal of Geography, Social, and Multicultural Education, 2024)
This research is a qualitative study that examines the impact of using ChatGPT on changes in student learning behavior. Behavior change is a process of movement carried out by individuals to adapt to the environment. This research used qualitative research methods and obtained 9 respondents. Data collection methods used observation and interview techniques. The results of this research show that ChatGPT has positive and negative impacts, using ChatGPT makes students quickly complete assignments, but this causes students to become increasingly dependent and lazy about reading articles and books, students will experience decreased literacy and have negative effects.